Impact Analysis of the Introduction of Glide Apps as Thematic Learning Media on Social Emotional Behavior of Elementary School Teachers - Julianto; Asri Susetyo Rukmi; Shinta Pramudya Kusuma Wardani (Universitas Nahdatul Ulama Surabaya, 2023)
The development of the times has become a separate demand for teachers in terms of varying learning media according to curriculum developments and integrating technology to facilitate teachers in fulfilling their duties as one of the important components of the advancement in Indonesia’s education sector. In this case, it is also necessary to know that the development of the teacher's social-emotional behavior also influences the quality of education. The purpose of this study is to determine the impact of introducing thematic learning media based on the Glide Apps startup on the social-emotional behavior of teachers. This research is a type of descriptive qualitative research. The sampling technique uses purposive sampling. Data collection methods used in this study were participatory passive observation. Data analysis techniques use Miles and Huberman model. Based on the results of the study it was found that there was an impact on the training as indicated by the achievement of social-emotional aspects such as affection, participation, communication, and interaction, adaptation, confidence, high curiosity, and expressing appropriate emotions. Calculation of the results from observation sheet score shows a very good category with a percentage score of 90.4% and a Likert scale score of 4.52. These results indicate that the introduction of Glide Apps-based learning media has a positive impact on the development of social-emotional behavior of elementary school teachers. Suggestions that can be given based on the results of the research are the need for a good preparation for unexpected things such as variations in questions and building positive energy to support good social-emotional behavior.